ELABORATION OF RECOMMENDATIONS FOR DEVELOPMENT AND SURVEY OF WELLS WITH THE AID OF JET DEVICES AFTER HYDRAULIC FRACTURING - A. E. Verisokin; G. A. Shlein (Наука. Инновации. Технологии)
Introduction. The paper provides recommendations for the development and survey of wells with the aid of jet devices, depending on the nature of the inflow after hydraulic fracturing. Existing solutions to develop and survey wells do not prevent complications after hydraulic fracturing, such as the active removal of proppant from the bottom-hole zone with the backfill of well bottom-hole and a decrease in well flow rates. The use of jet pumps of the design proposed in the work makes it possible to effectively develop wells, reduce the time of their commissioning, conduct high-quality hydrodynamic surveys and obtain reservoir iltration parameters. Materials and methods of research. To elaborate recommendations for the development and survey of wells, depending on the nature of the inflow after hydraulic fracturing, reports on operations at the wells of the Russian area, the Vostochno-Messoyakhskoye field, and the Yamburgskaya area were studied. The pressure build-up curve was processed at each well under study. The obtained data were processed by D. Horner's method. Research results and their discussion. The instruction for the operation of the jet pump is offered. The design of the developed low-through jet device is given. The operations that are documented with certiicates when testing wells using a jet pump are described. The experience of development and survey of wells, depending on the nature of the inflow, is presented. Three main reservoir drives in which deep oil samples are most often taken from wells were considered. Conclusions. The development of wells by jet devices after hydraulic fracturing showed the absence of proppant removal, stable operation of wells was pointed out. The promising directions of using jet devices are determined, depending on the nature of the inflow. These interpretations of hydrodynamic surveys of wells allow us to conclude that there are luid reservoirs in the considered intervals. The conditions for the selection of deep samples of hydrocarbons are considered.